Molecular signatures associated with tumor-specific immune response in melanoma patients treated with dendritic cell-based immunotherapy - García-Salum, Tamara; Hoheisel, Jörg D. (OncoTarget, 2018)
Oncotarget | https://doi.org/10.18632/oncotarget.24795 Tamara García-Salum, Andrea Villablanca, Franziska Matthäus, Andrés Tittarelli, Mauricio Baeza, Cristián Pereda, M. Alejandra Gleisner, Fermín E. González,...